Distinguishing Income from Substitution Effects in Disability Insurance - Autor, David H; Duggan, Mark G (American Economic Review, 2007)
A set of studies conducted over the last 15 years has produced a near consensus that the Social Security Disability Insurance system (SSDI) has substantial disincentive effects on the labor supply of near elderly males, diminishing labor force participation, increasing the sensitivity of labor force exit decisions to adverse economic shocks, and encouraging those nearing retirement to claim disability benefits and subsequently transfer into the Social Security retirement program. Yet, efforts by the Social Security Administration (SSA) to encourage labor supply among the disabled by removing the work disincentives built into SSDI have been almost entirely unsuccessful. Most notably, in 1999, Congress authorized the Ticket to Work program, which provides an array of inducements for current SSDI beneficiaries to take up employment, including permitting a trial work period of up to nine months, providing 7.75 years of ongoing Medicare eligibility following return to work, and providing three years of automatic benefit reinstatement when claimants’ workplace earnings fall below a threshold level. Each of these steps reduces the implicit tax placed on labor supply by the SSDI program. Despite these lures, fewer than 1,400 (0.01 percent) of the 12.2 million tickets issued to date have led to successful workforce integration (Autor and Duggan 2006).